IMPROVING STUDENTS’ SPEAKING SKILL THROUGH ROLE PLAY ACTIVITY BY USING HAND PUPPET - Fuji Kurniatun; Luwandi Suhartono; Wardah Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research is conducted on eighth grade students of SMP Pertiwi Pontianak in academic year 2013/2014. The researcher concerned on improving students’ speaking skill in term of accuracy in pronouncing the words and fluency in delivering the dialogues. Those were students’ problems in transactional conversation covers the expressing of asking and giving information, like and dislike, and asking, giving and refuse service. Role-playing technique by using hand puppet in form of dialogue facilitates students to have a chance in preparing, practicing and reflecting their speaking skill. The method of this research was classroom action research. The data on this research were collected by the use of observation and measurement technique. The observation checklist and field note were used to help the researcher in observing everything happened in teaching and learning activity. This research was done in three cycles. After applying role play technique by using hand puppet in form of dialogue, the students improved their accuracy in pronouncing the words and fluency in delivering the dialogues from cycle to cycle. Based on the research findings, the mean score of students’ speaking skill in the first cycle was 47.62 which was categorized as poor, in the second cycle was 56.85 which was still categorized as poor to average and finally in the third cycle was 71.73 which is categorized as average to good. In conclusion, role play technique by using hand puppet helped the teacher to teach her students to speak in English and encourage students to speak up in the classroom. Keyword : Hand Puppet, Role-Play, Speaking Skill